2002
DOI: 10.1007/s00268-002-6665-1
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Trial of Unilateral Surgery for Nonhereditary Medullary Thyroid Carcinoma in Patients without Germline RET Mutations

Abstract: Although sporadic medullary thyroid carcinoma (MTC) tends to be unicentric and confined to one lobe, total thyroidectomy is usually performed because of the risk of a hereditary or bilateral process. Germline RET mutation analysis can discriminate hereditary MTC and truly sporadic, nonhereditary MTC. We analyzed 72 of 94 patients with MTC to establish the genetic nature and the clinical features of nonhereditary MTC. Since 1996 we have prospectively treated 15 patients with nonhereditary MTC (prospective study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 24 publications
1
52
0
1
Order By: Relevance
“…Calcitonin values (basal or stimulated by pentagastrin, calcium, or both) are nearly always elevated with MTC. Similarly, an elevated calcitonin level after surgery is thought to be the first sign of persistent, recurrent or generalized disease [7,43].…”
Section: Medullary Thyroid Carcinomamentioning
confidence: 99%
“…Calcitonin values (basal or stimulated by pentagastrin, calcium, or both) are nearly always elevated with MTC. Similarly, an elevated calcitonin level after surgery is thought to be the first sign of persistent, recurrent or generalized disease [7,43].…”
Section: Medullary Thyroid Carcinomamentioning
confidence: 99%
“…Multivariable analysis by Pelizzo et al [7] has shown that total thyroidectomy was correlated with better survival and that the few cases of prolonged disease-free survival after isthmolobectomy were not sufficient to justify anything less than total thyroidectomy because of the limited number of patients [18].…”
Section: Thyroidectomymentioning
confidence: 99%
“…14 However, in spite of these observations, it has been argued that when pre-operative mutational analysis has shown no RET germline mutation there may be a case for performing only hemithyroidectomy and isthmusectomy. In a group of highly selected patients with sporadic tumours, Miyauchi and colleagues 15 were able to demonstrate that successful outcome and biochemical cure with a normal postoperative calcitonin level were not compromised by performing unilateral resection. However, 18.3% of their series had intraglandular metastatic spread but these were all cases noted to have extensive nodal metastases.…”
Section: Extent Of Thyroidectomymentioning
confidence: 99%